The Identification of B-Ocimene Biosynthetic Pathway Through Mevalonate Acid (MVA) and 1-Deoxy-D-Xylulose 5-Phosphate (DXP) Pathways Using Crude Enzyme Extracts in Indonesian Bay Leaf/Salam Leaf (Syzygium polyanthum) - Bima Putra Pratama; Yudi Pranoto; Supriyadi; Respati Tri Swasono (Tropical Life Sciences Research, 2022)
Salam leaf has a ?-ocimene as a key volatile compound that gives a fresh aroma to the food when the salam leaves are involved in the cooking process. As a secondary metabolic product, enzymatic biosynthesis as the early stage of ?-ocimene is a factor that needs to be known. Thus, this study was done to identify the mechanism of the two well-known terpenoid biosynthetic pathways, namely MVA and DXP pathways, in the biosynthesis of ?-ocimene in salam leaves. The activity of the 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR)-MVA pathway-determining enzyme and 1-deoxy-Dxylulose- 5-phosphate synthase (DXS)-DXP pathway-determining enzyme in the crude enzyme and their derivative products of salam leaves were analysed for their changes by differences of substrate ratios and enzyme inhibitors. The results showed that the activity of the HMGR enzyme was lower significantly than the DXS enzyme based on the addition of variations to the substrate ratio. These results were also supported by the enzyme and substrate reaction products, MVA and IPP intermediates from the MVA pathway, which were significantly lower when compared to DXP and IPP intermediates from the DXP pathway. As the end product of the reaction, ?-ocimene gave a significantly higher value of the DXP pathway than the MVA pathway. Therefore, it can conclude that the mechanism of the biosynthetic pathway of ?-ocimene in salam leaves was synthesised via the DXP pathway. The production of ?-ocimene could have crosstalk-pathway through the MVA pathway, especially when the DXP pathway was blocked.